Problems relating to the export of Peninsular Malaysia main primary commodities / Ahmad Jaafar - Jaafar, Ahmad (1985)
Export of main primary commodities of Pennisular Malaysia have helped, our country and dominated a lo t to our economy and also to our country’s development. Those exports play a bigger role in providing income for Pennisular Malaysia. With the increase in exports of our main primary commodities that is rubber, palm oil and timber our economy will be more stable and thus will help in building up our nation . Problems arising from the export of these main commodities will affect the performance and thus affect the development of our country.